2021
DOI: 10.1002/bimj.202100081
|View full text |Cite
|
Sign up to set email alerts
|

Power considerations for generalized estimating equations analyses of four‐level cluster randomized trials

Abstract: In this article, we develop methods for sample size and power calculations in four‐level intervention studies when intervention assignment is carried out at any level, with a particular focus on cluster randomized trials (CRTs). CRTs involving four levels are becoming popular in healthcare research, where the effects are measured, for example, from evaluations (level 1) within participants (level 2) in divisions (level 3) that are nested in clusters (level 4). In such multilevel CRTs, we consider three types o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 36 publications
3
30
0
Order By: Relevance
“…Oftentimes, primary analysis of CRTs proceeds without covariates; in this case Z ij only includes a cluster-level intervention indicator (p = 1), so V F G and V KC would be numerically identical if Ω i V m does not exceed the constant r, even though their values are generally different otherwise. The above derivations are also compatible with the insight in Ziegler (2011) that the KC sandwich variance can be derived as a modified version of the FG sandwich variance, and the numerical evidence in Wang et al (2021) that these two often have similar finite-sample operating characteristics for GEE analyses of non-censored outcomes. A final multiplicative bias-correction is analogous to Mancl and DeRouen (2001), and assumes that the last term of ( 8) is negligible, which then gives…”
Section: Bias Corrections Based On Methods For Generalized Estimating...supporting
confidence: 82%
See 3 more Smart Citations
“…Oftentimes, primary analysis of CRTs proceeds without covariates; in this case Z ij only includes a cluster-level intervention indicator (p = 1), so V F G and V KC would be numerically identical if Ω i V m does not exceed the constant r, even though their values are generally different otherwise. The above derivations are also compatible with the insight in Ziegler (2011) that the KC sandwich variance can be derived as a modified version of the FG sandwich variance, and the numerical evidence in Wang et al (2021) that these two often have similar finite-sample operating characteristics for GEE analyses of non-censored outcomes. A final multiplicative bias-correction is analogous to Mancl and DeRouen (2001), and assumes that the last term of ( 8) is negligible, which then gives…”
Section: Bias Corrections Based On Methods For Generalized Estimating...supporting
confidence: 82%
“…We then generalize the class of multiplicative bias corrections developed for GEE to the sandwich variance estimator under the marginal Cox model. Following Wang et al (2021), the class of multiplicative bias corrections generally takes the form of…”
Section: Bias Corrections Based On Methods For Generalized Estimating...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of population-averaged models with GEE analysis, simple-to-use sample size formulae for continuous responses and non-simulation procedures for binary responses have recently been proposed for complete, cross-sectional and cohort SW-CRTs within the framework of GEE [Li et al, 2018]. The methods extend earlier sample size formulae for GEE analysis of parallel-groups CRTs, including cross-sectional and cohort CRTs [Preisser et al, 2003[Preisser et al, , 2007 and multi-level CRTs [Reboussin et al, 2012, Teerenstra et al, 2010, Wang et al, 2021. Prior work [Li et al, 2018, Li, 2020 has shown that the analytical power for marginal mean (e.g, intervention) parameters in complete SW-CRTs agrees well with simulated power based on GEE with finite-sample sandwich variance estimators for as few as eight clusters [Li et al, 2018].…”
Section: Introductionmentioning
confidence: 99%